The Possible sources of /z/ in AO (2012)
The place of Ao among Yoruba dialects has been clearly identified in previous research. Its location within the South Eastern Yoruba (SEY) of Awobuluyi (1998) has been incontrovertibly established. However, the dialect has two phonemic consonants which distinguish it from the other dialects of Yoruba. These are /z/: The voiced alveolar fricative, and /λ/: The voiced post-alveolar fricative. This paper focuses on the possible source of /z/ in the sound system of Ao. Three possibilities are explored. These are: spirantisation, affrication and the effect of neighbouring Edoid languages. On the basis of phonological plausibility, the researcher cleaves to the first possibility spirantisation, otherwise known as frication